2019
DOI: 10.3390/ijms20081925
|View full text |Cite
|
Sign up to set email alerts
|

A Small In Vitro Fermentation Model for Screening the Gut Microbiota Effects of Different Fiber Preparations

Abstract: The development of prebiotic fibers requires fast high-throughput screening of their effects on the gut microbiota. We demonstrated the applicability of a mictotiter plate in the in vitro fermentation models for the screening of potentially-prebiotic dietary fibers. The effects of seven rye bran-, oat- and linseed-derived fiber preparations on the human fecal microbiota composition and short-chain fatty acid production were studied. The model was also used to study whether fibers can alleviate the harmful effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 76 publications
3
32
0
Order By: Relevance
“…Blautia genus was a short-chain fatty acid (SCFA) producing genus, and it was reported to be a beneficial bacterium negatively associated with metabolic syndromes, with its mainly biological function thought to be producing butyrate [27]. Although we did not test the concentration of SCFA in fecal or serum samples, the observed enrichment of Blautia genus following oatmeal consumption matched up to the result of increased fecal butyrate concentration from previously reported in vitro fermentation studies and animal experiments [28][29][30]. Besides, considerable evidences have reported that SCFA, especially butyrate, might participate in cholesterol metabolism in various ways, such as inhibiting intestinal cholesterol absorption [31], increasing fecal excretion of bile acid [32,33] as well as promoting uptake and metabolize cholesterol from blood [32].…”
Section: Discussionmentioning
confidence: 56%
“…Blautia genus was a short-chain fatty acid (SCFA) producing genus, and it was reported to be a beneficial bacterium negatively associated with metabolic syndromes, with its mainly biological function thought to be producing butyrate [27]. Although we did not test the concentration of SCFA in fecal or serum samples, the observed enrichment of Blautia genus following oatmeal consumption matched up to the result of increased fecal butyrate concentration from previously reported in vitro fermentation studies and animal experiments [28][29][30]. Besides, considerable evidences have reported that SCFA, especially butyrate, might participate in cholesterol metabolism in various ways, such as inhibiting intestinal cholesterol absorption [31], increasing fecal excretion of bile acid [32,33] as well as promoting uptake and metabolize cholesterol from blood [32].…”
Section: Discussionmentioning
confidence: 56%
“…The abundance of lactobacilli increased in the presence of xylo-oligosaccharides and INU when compared to control without fibre or to the microcrystalline CEL, while resistant starch increased the Bacteroidaecae family. Moreover, in that study, these fibres decreased the relative abundance of the Lachnospiraceae family [48]. Inulin has a demonstrated effect on the growth of bifidobacteria both in vitro [49] and in vivo [50][51][52], highlighting the relevance of batch incubations for initial screening purposes.…”
Section: Discussionmentioning
confidence: 60%
“…and previous in vitro studies have suggested that the presence of glucose increases phenolic acid production from quercetin in fermentations [15,19], which is likely to be via its effect on the microbial catabolism or composition. We did not measure bacterial populations in this study but in studies by others, 16S rDNA profiling has previously that the static batch incubation model is useful to mimic colon microbial processes and is widely used to assess the impact of dietary factors on bacterial metabolism in a reproducible fashion for high throughput studies [48]. The abundance of lactobacilli increased in the presence of xylo-oligosaccharides and INU when compared to control without fibre or to the microcrystalline CEL, while resistant starch increased the Bacteroidaecae family.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, previous studies have reported that the pH is lowest in the proximal colon (~5.6) and increases towards the distal colon (~6.3) [1,60], which indicates that the pH changes in this study are within a reasonable range. Although the host colonic environment cannot be completely reproduced in the in vitro studies, in vitro models are practical tools for the investigation of the alteration of microbiota in response to exposure to different compounds [61]. Another limitation in this study was that we could not distinguish the butyrate produced via butyrate-producing bacteria vs. that resulting from B-FOS breakdown.…”
Section: B-mentioning
confidence: 98%